Effects of exercise therapy with blood flow restriction on shoulder strength: protocol for a systematic review and meta-analysis - Mohammad Amin Gholipour; Hediyeh Hamedi; Tahere Seyedhoseinpoor (BMJ Open)
Introduction Blood flow restriction therapy (BFRT) has gained attention for its capacity to induce substantial muscle hypertrophy and strength gains even when employing relatively minimal loads. Strength training is of significant importance in the rehabilitation of patients experiencing shoulder pain, which may arise from a multitude of sources, including rotator cuff injuries, tendinopathies or postsurgical recovery. However, traditional resistance training can be challenging for these individuals due to the presence of pain and functional limitations. In this regard, BFRT in conjunction with low-load strength training may prove an efficacious alternative. The integration of BFRT into rehabilitation protocols for shoulder pain could provide a viable pathway to improving muscle strength and facilitating recovery while minimising the risk of exacerbating pain or injury. The primary objective of this study is to conduct a systematic review of the effects of training with BFRT of the upper limb on shoulder strength.Methods and analysis A comprehensive database search will be conducted across multiple platforms, including PubMed, Scopus, Ovid, Web of Science, EBSCO, Cochrane Central, PEDro and Google Scholar, using predefined key terms without any language restriction. The particular focus of the study will be clinical trials with a controlled group that assess the impact of BFRT on upper extremity, neck and trunk muscles in both healthy individuals and patients. The primary outcome measure will be shoulder strength and power in different directions. The Cochrane Collaboration’s Risk of Bias 2 tool will be employed for the purpose of evaluating the risk of bias inherent to the studies in question. A meta-analysis will be conducted using Stata software. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach will be employed to evaluate the quality of evidence for the primary outcomes.Ethics and dissemination The previously published papers will be used for all analyses in this study. Results will be disseminated through professional networks, presentations at conferences and publication in a peer-reviewed journal. No ethics approval is required.PROSPERO registration number CRD42024605189.